ANALISIS PENGENDALIAN INTERNAL DAN PIUTANG DAGANG TERHADAP HUTANG DAGANG DI CV MALIVI ENG - RAHEL JUNITA (LP2MTBM MAKARIOZ, 2023)
There has been an increase in production control costs that cannot be controlled by CV Melvi Eng's internal auditors, thus increasing large financing and impacting on CV Melvi Eng's inability to increase capital and profits in large quantities, where the large cost of production control also makes CV Melvi Eng's trade receivables also decrease and will make accounts payable increase and will make CV Melvi Eng difficult to increase liquidity for Business development and production that causes production to decrease and the company will not be able to increase profits optimally. This study aims to determine whether the control of production costs and accounts receivable, either partially, or simultaneously has a significant effect on CV Melvi Eng's accounts payable. Data analysis in this study uses descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests, where the population in this study is the quarterly financial statements of PT CV Melvi Eng in 2015-2022, While the sampling method in this study used purposive sampling. The results of this study stated that simultaneously controlling production costs and trade receivables had a significant effect on CV Melvi Eng's accounts payable, while partially only variable accounts receivable had a significant effect on CV Melvi Eng's accounts payable